1992
DOI: 10.1063/1.463799
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of CO2–D(H)Br: Molecular structure and its reliability

Abstract: A high resolution rovibrational absorption spectrum of the weakly bonded CO2–DBr complex has been recorded in the 2350 cm−1 region by exciting the CO2 asymmetric stretch vibration with a tunable diode laser. The CO2–DBr band origin associated with this mode is 2348.2710 cm−1, red-shifted by 0.87 cm−1 from uncomplexed CO2. The position of the hydrogen atom is determined from differences in moments-of-inertia between CO2–DBr and CO2–HBr, i.e., by using the Kraitchman method. From this, we conclude that ground st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…18 Such interactions are well-known for sp 2 -hybridized C-atoms in carbonyls [19][20][21][22][23][24][25][26] and have recently been reported for the sphybridized C-atoms of (coordinated) acetonitrile, 27 carbon monoxide 28 and carbon dioxide. [29][30][31][32] Non-covalent interactions with sp 3 -hybridized carbon atoms are implicated in the advent of canonical S N 2 nucleophilic displacement reactions 12,[33][34][35] and can persist with methyl groups in crystal structures. [36][37][38] However, a supramolecular synthon to predictably generate directional tetrel-bonding interactions centred on sp 3 -C has not yet been experimentally disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…18 Such interactions are well-known for sp 2 -hybridized C-atoms in carbonyls [19][20][21][22][23][24][25][26] and have recently been reported for the sphybridized C-atoms of (coordinated) acetonitrile, 27 carbon monoxide 28 and carbon dioxide. [29][30][31][32] Non-covalent interactions with sp 3 -hybridized carbon atoms are implicated in the advent of canonical S N 2 nucleophilic displacement reactions 12,[33][34][35] and can persist with methyl groups in crystal structures. [36][37][38] However, a supramolecular synthon to predictably generate directional tetrel-bonding interactions centred on sp 3 -C has not yet been experimentally disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…In 1984, Klemperer et al confirmed, via microwave spectral analysis, that the equilibrium geometry of the adduct features a tetrel bond, i.e., that the tetrelbonded O 2 C···OH 2 geometry is preferred to the hydrogenbonded HO-H···O=CO geometry [35]. During the 1980s, tetrel bonding was shown to be more important than hydrogen bonding for driving the formation of other lowest-energy complexes formed by carbon dioxide, for instance those with HBr [36] and HCN [37]. Most papers on the ability of tetrels to function as electrophiles describe theoretical investigations of interactions involving carbon [38] and silicon [39][40][41], whereas investigations of the heavier group 14 elements are far less frequent [42].…”
Section: Introductionmentioning
confidence: 99%
“…Rotational spectroscopy can contribute to recognize, identify, and characterize these interactions, simultaneously offering comparison with more common HBs and between gas and condensed phases, where most of the previous information was obtained . Among the initial rotational studies on HBs some neutral heterodimers were early recognized as unfitting to HB patterns, as the S⋅⋅⋅N, N⋅⋅⋅C, and C⋅⋅⋅Br interactions reviewed by Legon . Specific searches for XBs/CBs/NBs/TBs are now appearing at slow pace.…”
Section: Chalcogen Pnicogen and Tetrel Bondsmentioning
confidence: 99%
“…The electrostatic argument was later generalized to explain experimental observations into the new conceptual frames of chalcogen bonds (CB), pnicogen bonds (NB), tetrel bonds (TB), involving atoms of Groups 14, 15, and 16 or even coinage‐metals in R−A⋅⋅⋅B bridging interactions formally analogue to the HB or XB (R−H/X⋅⋅⋅B). Legon has noticed ironically that rotational and vibrational experiments existed for the new bonds long before they had a name, occasionally being called “anti‐hydrogen bond” . This extension of the chemical discourse makes NCIs more diverse and attractive than ever.…”
Section: Introductionmentioning
confidence: 99%